Association of Health Literacy With Medication Adherence Mediated by Cognitive Function Among the Community-Based Elders With Chronic Disease in Beijing of China - Jia, Qiaoling; Wang, Haiyan; Wang, Li; Wang, Yanhong (Frontiers in Public Health, 2022)
Background: Although health literacy was considered to play a crucial role in NCD prevention and control, the relationship of health literacy and medication adherence has rarely given attention among elderly Chinese population in previous studies, especially considered that they might be with cognitive impairment. Purpose: The aim of this study was to investigate the association between health literacy and medication adherence and mediation by cognitive ability among community-based elders with chronic disease in Beijing of China. Methods: The elderly aged 60 years old or over were recruited in cross-sectional survey conducted in Beijing of China by using multistage, stratified sampling method. Of those, the participants with chronic disease and need to take long-term medicine were included in our study. The information about sociodemographic characteristics, health literacy, cognition ability, and medication adherence were collected by the questionnaire. The univariate and multiple logistic regression analysis were used to measure the association of health literacy and adherence medication, and mediate effect by cognitive ability. Results: The total of 4166 elder populations (average age: 70.61±7.38 years) were included in this study, 1395 participants (33.49%) were non-adherence, 1983 participants (47.60%) had two chronic conditions or more, and 1459 participants (35.02%) screened as cognitive impairment. The health literacy was negatively associated with medication adherence. The lower total scores of health literacy were found with high risk of non-adherence (p<0.01, adjust OR=0.988 per one point increase, 95%CI: 0.982-0.993) controlling other covariates. But their association tended to be weakened or even disappeared among the elder with cognitive impairment compared to those of the populations with normal cognitive. Conclusions: Improving health literacy might a public health strategy to increase medication adherence of elders, but need to firstly identified the potential target population based on their cognitive ability.